Longitudinal and transverse coupling in infrared gold nanoantenna arrays: long range versus short range interaction regimes - Weber, Daniel; Albella, Pablo; Alonso-González, Pablo; Neubrech, Frank; Gui, Han; Nagao, Tadaaki; Hillenbrand, Rainer; Aizpurua, Javier; Pucci, Annemarie (Optics express, 2011)
Interaction between micrometer-long nanoantennas within an array considerably modifies the plasmonic resonant behaviour; for fundamental resonances in the infrared already at micrometer distances. In order to get systematic knowledge on the relationship between infrared plasmonic resonances and separation distances dx and dy in longitudinal and transverse direction, respectively, we experimentally studied the optical extinction spectra for rectangularly ordered lithographic gold nanorod arrays on silicon wafers. For small dy, strong broadening of resonances and strongly decreased values of far-field extinction are detected which come along with a decreased near-field intensity, as indicated by near-field amplitude maps of the interacting nanoantennas. In contrast, near-field interaction over small dx does only marginally broaden the resonance. Our findings set a path for optimum design of rectangular nanorod lattices for surface enhanced infrared spectroscopy.